Millennium development goals : achieving the millennium development goals with equality in Latin America and the Caribbean : progress and challenges (UN New YorkUS, 2010)
Presents a second comprehensive assessment of the region's progress towards the Millennium Development Goals.
Includes summary -02.01.01 M646s.